The new Ray Bradbury review. - Touponce, William F.; Spiech, David E. (New Ray Bradbury review ;, 2008)
"The New Ray Bradbury Review, echoing William F. Nolan's inaugural one-volume review published in 1952, is the first journal to be dedicated annually to the life and writings of one of America's most prolific and popular authors ... designed primarily to study the impact of Ray Bradbury's writings on American culture."